On octahedrality and Müntz spaces - Martiny, André (MATHEMATICA SCANDINAVICA, 2020)
We show that every Müntz space can be written as a direct sum of Banach spaces X and Y, where Y is almost isometric to a subspace of c and X is finite dimensional. We apply this to show that no Müntz space is locally octahedral or almost square.